Update on Molecular Testing in von Willebrand Disease - Batlle, Javier; Pérez-Rodríguez, Almudena; Corrales, Irene; Borràs, Nina; Costa Pinto, Joana; López-Fernández, María Fernanda; Vidal, Francisco; on behalf of PCM-EVW-ES Investigators Team (Seminars in Thrombosis and Hemostasis, 2019)
Diagnosis of von Willebrand disease (VWD) depends on personal and family history of bleeding and confirmatory laboratory testing. Currently available phenotypic tests for VWD contain potential sources for error that may distort results. Despite an exponential growth of information about the von Willebrand factor gene (VWF), the role of molecular diagnosis in VWD is still controversial. Due to the complexity and high cost of conventional molecular analyses, some investigators have recommended limiting this approach to distinguish suspected type 2N VWD from hemophilia A, type 2B from platelet-type VWD, and the exploration of type 3 VWD. New genetic methodologies and approaches are becoming available, but there is still some reluctance for their implementation in VWD diagnosis. This article discusses the pros and cons of molecular testing in VWD considering the experience obtained through the multicenter project “Molecular and Clinical Profile of VWD in Spain (PCM-EVW-ES).”
Keywords: von Willebrand disease; von Willebrand factor; diagnosis; phenotype; molecular testing